Model Checking Software 17th International SPIN Workshop, Enschede, The Netherlands, September 27-29, 2010. Proceedings - Pol, Jaco.; Weber, Michael. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 17th International SPIN workshop on Model Checking Software, SPIN 2010, held at the University of Twente, in Enschede, The Netherlands, in September 2010. The 13 revised full papers presented together with 2 tool papers and 3 invited talks were carefully reviewed and selected from 33 submissions. The papers are organized in topical sections on satisfiability modulo theories for model checking, model checking in context (simulation, testing, UML), implementation and performance of model checking, LTL and B<U+00fc>chi automata, extensions to infinite-state systems, and concurrent software.